2017
DOI: 10.1111/vop.12518
|View full text |Cite
|
Sign up to set email alerts
|

Canine central corneal thickness measurements via Pentacam‐HR®, optical coherence tomography (Optovue iVue®), and high‐resolution ultrasound biomicroscopy

Abstract: Considering there is an average of 7.5% normal diurnal variation in canine CCT, a 3.0% difference between Pentacam and SD-OCT values is likely not clinically relevant. However, Pentacam measurements were both statistically and clinically significantly different from UBM and SD-OCT measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
7
2
Order By: Relevance
“…A recent study compared the Pentacam to UBM and SD-OCT, finding that the Pentacam was clinically similar in measurement to the values obtained by SD-OCT, but there were significant differences in the values obtained via UBM. 13 Although CCT values have been previously reported to increase with age, 34,35,37 the current study found no significant difference between age groups. However, when comparing the youngest group of dogs to the older two together, the difference approached significance with a P-value of 0.055.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…A recent study compared the Pentacam to UBM and SD-OCT, finding that the Pentacam was clinically similar in measurement to the values obtained by SD-OCT, but there were significant differences in the values obtained via UBM. 13 Although CCT values have been previously reported to increase with age, 34,35,37 the current study found no significant difference between age groups. However, when comparing the youngest group of dogs to the older two together, the difference approached significance with a P-value of 0.055.…”
Section: Discussioncontrasting
confidence: 63%
“…While no direct comparison was made in this study, the results found with the Pentacam are similar for CCT. A recent study compared the Pentacam to UBM and SD‐OCT, finding that the Pentacam was clinically similar in measurement to the values obtained by SD‐OCT, but there were significant differences in the values obtained via UBM . Although CCT values have been previously reported to increase with age, the current study found no significant difference between age groups.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…However, the small sample size remains a limitation, and further studies are needed to determine whether the differences in the CCT between species are related to factors such as genetic and environmental factors. The SD‐OCT unit used in this study calculated the CCT not as the thickness of a specific point, but as the mean thickness of a specific area 3,25 . If the corneal thickness was thin below a certain standard, the machine did not automatically recognize the thickness.…”
Section: Discussionmentioning
confidence: 99%
“…It evaluates both the anterior and posterior corneal surfaces and provides a variety of outputs, including total corneal refractive power (TCRP) and true net power (TNP) maps . The Pentacam has been used in veterinary medicine to establish normal anterior segment values in rabbits, cats, and dogs, but has yet to be used in a hypothesis‐driven clinical study.…”
Section: Introductionmentioning
confidence: 99%